Educación y música: banda instrumental escuela de Riojalandia - Solera Salas, Mario (2013)
Based on research done at the School of Riojalandia, Barranca, Puntarenas, the article provides criteria of various authors on the contributions of music, both in the classroom and instrumental ensembles, in schools and colleges. As a sign of the exposed theory, provides an analysis of the management impact of the group Banda Instrumental Escuela de Riojalandia, both in this school and its own members